ANALISIS KAUSALITAS EKSPOR NON MIGAS DENGAN PERTUMBUHAN EKONOMI MENGGUNAKAN METODE FINAL PREDICTION ERROR - Maulidyah Indira Hasmarini; Dwi Murtiningsih (Jurnal Ekonomi Pembangunan: Kajian Masalah Ekonomi dan Pembangunan, 2003)
This research titled "Causality analysis non petrol export with economic growth using final error prediction methods". Goal which needs to find the answer in this research is to know that non petrol export variable affecting to economic growth variable and economic growth variable affecting non petrol export variable. And also to know final prediction error with existence of long term equilibrium between non petrol export with economic growth. Hypothesis proposed is non petrol export having positive effect to economic growth and economic growth have positive effect to non petrol export. Final error prediction with existence of relation between long term equilibrium and non petrol export and economic growth have positive effect, and final error prediction with existence of relation between long term equilibrium with economic growth and non petrol export have positive effect.Based on analysis there's only one direction causality relation between economic growth and non petrol export. From facts above can be concluded that economic growth will bring creation process and expanding strong domestic market because export is not a starting point or initial destination of economic growth but export only a economic growth process